Effect of Transplantation of Bone Marrow Derived Mesenchymal Stem Cells and Platelets Rich Plasma on Experimental Model of Radiation Induced Oral Mucosal Injury in Albino Rats - Basma Elsaadany; Samar El Kholy; Dalia El Rouby; Laila Rashed; Tarek Shouman (International Journal of Dentistry)
Normal tissue damage following radiotherapy is still a major problem in cancer treatment. Therefore, the current work aimed at exploring the possible role of systemically injected bone marrow derived mesenchymal stem cells (BM-MSCs) and/or locally injected platelet rich plasma (PRP) in ameliorating the side effects of ionizing radiation on the rat’s tongue. Twelve rats served as control group (N) and 48 rats received a single radiation dose of 13 Gy to the head and neck region; then, they were equally divided into 4 experimental groups: irradiated only (C), irradiated + MSCs (S), irradiated + (PRP) (P), and combined group (PS). Animal scarification occurred in 3 and 7 days after radiation. Then, tongues were dissected and examined histologically and for expression of bcl-2 by RT-PCR. Histological examination of the treated groups (S), (P), and (PS) revealed an obvious improvement in the histological structure of the tongue, compared to group (C), in addition to upregulated expression of bcl-2, indicating decreased apoptotic activity. Conclusion. BM-MSCs and PRP have shown positive effect in minimizing the epithelial atrophy of normal oral mucosa after regional radiotherapy, which was emphasized by decreasing apoptotic activity in these tissues. Nevertheless, combined use of BM-MSCs and PRP did not reveal the assumed synergetic effect in oral tissue protection.